PEMBUATAN MEDIA PEMBELAJARAN BERBASIS BROWSER TRAINING DENGAN MENGGUNAKAN SOFTWARE CONTENT MANAGEMENT SYSTEM JOOMLA PADA MATA DIKLAT PEMELIHARAAN/SERVIS TRANSMISI MANUAL DAN KOMPONEN - Prabowo, Ruli Silo; Budi, Aris; Aryadi, Widya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2009)
Purpose of this research is to design, makes, and tests software in the form of studymedia of Browser Based Training ocular study manual transmission keeping/service andcomponent applies Content Management System JOOMLA in the form of CD (CompactDisk) to assist study. Research type applied in this research is experiment of prototype,while focusing research is how to designing, makes, and tests study media of E-Learningbases on Based Training at ocular study manual transmission keeping/service andcomponent applies Content Management System JOOMLA. Location of This research isBalai Pengembangan Multimedia (BPM) and SMK N IV Semarang. From test result triesdone, technical grade of this program included in good criterion with percentage of81,33%. While for program appearance, this program included in good criterion withpercentage of 80,00%. According to teacher SMK N 4 Semarang, in general educationcriterion of this program included in good criterion and as according to curriculumapplied.Kata kunci: Study Media, Browser Based Training, Manual Transmission